2020
DOI: 10.1186/s42779-020-00059-z
|View full text |Cite
|
Sign up to set email alerts
|

The enterprise culture heritage of Minangkabau cuisine, West Sumatra of Indonesia as a source of sustainable competitive advantage

Abstract: The enterprise cultural heritage of the Minangkabau cuisine, West Sumatra in Indonesia was formed by several factors such as history, knowledge, and inheritance of processing procedures to the presentation of cuisine. Minangkabau cuisine has a wealth of assets in the form of heterogeneity of culinary heritage resources that are thick with a unique value of a unique taste. Thus, Minangkabau cuisine with its cultural heritage becomes the strength of cultural identity for the Minangkabau people in the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…The dominant colors displayed are yellow, red, and green which also have meanings taken from Islamic Malay culture. It is in line with the results of research by Barney (2007); Mardatillah (2020;2021) that a highly competitive product can provide different added value than competitors so that consumers not only enjoy the product physically but also the philosophical meaning contained therein. Then the product will have a unique indigenous-based appeal that affects the company's marketing performance improvement (Setyawati, 2018).…”
Section: Resultssupporting
confidence: 84%
“…The dominant colors displayed are yellow, red, and green which also have meanings taken from Islamic Malay culture. It is in line with the results of research by Barney (2007); Mardatillah (2020;2021) that a highly competitive product can provide different added value than competitors so that consumers not only enjoy the product physically but also the philosophical meaning contained therein. Then the product will have a unique indigenous-based appeal that affects the company's marketing performance improvement (Setyawati, 2018).…”
Section: Resultssupporting
confidence: 84%
“…These regional quality certificates result in important social and economic benefits that aid in promoting rural areas, as well as providing extra income and support to combat unfair competition, while at the same time raising restaurant clients’ awareness of this problem [ 97 ]. These official designations boost the gastronomic tourism sector around specific food produce and recipes [ 22 ], to such an extent that governments and diverse institutions recognize the value of gastronomy as a seal of local authenticity and identity, thus protecting the products, promoting ecological awareness and the healthy and sustainable use of agri-food products, and stimulating inter-culturalism [ 10 , 59 , 83 ].…”
Section: Conceptualizing the Researchmentioning
confidence: 99%
“…Thus, tourists perceive, in effect, the restaurant subsector as an important attribute of the destination. Therefore, the quality of the gastronomy and service, along with the physical surroundings, can all produce a profound sensory and cultural experience of significant impact and level of satisfaction, whose several case studies have demonstrated, as in New Zeland [ 5 ], Ireland [ 22 , 23 ], India [ 4 ], China [ 15 ], Italy [ 28 ], Colombia [ 84 ] and Indonesia [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Minangkabau people believe that some of their customs cannot change, although others can change because they adapt to the times [18]. It is impossible to separate culture from people's lives since culture is closely related to the beliefs, norms, attitudes, and behaviors that are accepted by members of community groups and then engrained in daily behavior [23].…”
Section: Modernisationmentioning
confidence: 99%